Effect of Aging Temperature and time on the Transformation Behavior of a Ti-50.8 at.% Ni Alloy with Small Grains. (2015) - Wang, X.; Verlinden, B.; Van Humbeeck, J.
Abstract: A Ti-50.8 at.% Ni alloy with small grains (average grain size of 1.8 μm) was subjected to various aging treatments. It is found that the frequently reported multi-stage martensitic transformation, i.e. the transformation including two B19' martensite or two rhombohedral R-phase transformations, is absent in this study. The samples aged at 523–573 K show a single stage austenite↔R-phase transformation. A normal austenite→R-phase→martensite transformation is detected in the samples aged at 623–823 K. The origin of this phenomenon and the effect of grain size on the aging microstructure is discussed.